Influence of vegetable oil in the viscosity of biodiesel-a review - Tsuji, Fernando Kazushi [UNESP]; Neto, Luiz Daré [UNESP] (SAE International, 2008)
Viscosity is a measure fluid resistance to flowing, affecting the fuel spray in the combustion chamber and, by this way, thus the formation of carbon deposits. The analysis of the influence of vegetable oil viscosity in biodiesel seems appropriate, because biodiesel viscosity is a function of vegetable oil. The increase of the fuel viscosity, promoted by biodiesel, has a major impact on the dynamics of jet fuel, increasing its speed and distance of penetration, obtaining therefore an increase in the amount of turbulent movement of the jet and thus an increase in the rate of preparation of the mixture, air-fuel, when adding biodiesel to diesel oil. The negative effect of this higher fuel viscosity is the increase of the wear of the train of gears, cam shaft, and valve push rod of all the injection pumps due to the higher pressure of injection. The viscosity of biodiesel is influenced by the size of its molecule and by the increase of molecule insaturations, is directly related with its origin vegetable oil or fat. This study is a review of the influence of vegetable oils in viscosity of biodiesel. Copyright © 2008 SAE International.
Keywords: Carbon deposites; Diesel oil; Fluid resistance; Fuel sprays; Fuel viscosity; Injection pump; Air; Combustion chambers; Diesel fuels; Fuels; Molecules; Vegetable oils; Viscometers; Biodiesel